Risk Factors for the Occurrence of Rebound Pain After Intercostal Nerves Block in Three-Port Thoracoscopic Surgery: A Case-Control Study - Wan C; Kong M; Shen Q; Lu W; Shen X (Journal of Pain Research)
Chongyang Wan,1,2 Min Kong,2 Qihong Shen,2 Weina Lu,1,2 Xu Shen2 1Jiaxing University Master’s Degree Cultivation Base, Zhejiang Chinese Medical University, Jiaxing City, Zhejiang Province, People’s Republic of China; 2Department of Anesthesiology and Pain Research Center, The Affiliated Hospital of Jiaxing University, Jiaxing City, Zhejiang Province, People’s Republic of ChinaCorrespondence: Xu Shen, Medical Center for Anesthesia and Pain, First Hospital of Jiaxing, 1882 Zhonghuan South Road, Nanhu District, Jiaxing City, Zhejiang Province, People’s Republic of China, Email 00181787@zjxu.edu.cnBackground and Objectives: Rebound pain (RP), characterised by an acute increase in pain levels, is usually observed after the effects of block anaesthesia have subsided. Severe RP can cause adverse effects, thus affecting patient prognosis. In this study, we investigated the incidence of RP and its risk factors after intercostal nerve block in three-port thoracoscopic surgery to provide a clinical basis for identifying high-risk patients and providing early intervention.Methods: A single-centre retrospective study was conducted on 475 patients who underwent three-hole thoracoscopic surgery from September 2022 to September 2023 in Jiaxing First Hospital. Data were collected and compared between patients who developed RP and those who did not. IBM SPSS Statistics 25.0 software was used for statistical analysis.Results: Data were collected from 700 patients. After applying the exclusion criteria, 475 cases were finally included and the incidence of RP was 23.8%. The results showed that the differences in body mass index (BMI), upper and lower chest diameters, anterior and posterior chest diameters, left and right chest diameters, and gender between patients with RP and those without RP were statistically significant (p < 0.05). In addition, the proportion of female patients with RP was significantly higher. BMI (advantage ratio [OR] = 0.835, 95% confidence interval [CI]: 0.375 ~ 1.859), upper and lower chest diameters (OR = 0.916, 95% CI: 0.827 ~ 1.014), anterior and posterior chest diameters (OR = 0.765, 95% CI: 0.635 ~ 0.921), left and right chest diameters (OR = 0.612, 95% CI: 0.421 ~ 0.891), and gender (OR = 1.170, 95% CI: 0.576 ~ 2.373).Conclusion: The incidence of RP after three-hole thoracoscopic intercostal nerve block is high and associated with multiple risk factors. Early intervention is needed for patients at risk of RP to improve patient prognosis and satisfaction.Keywords: intercostal nerve block, rebound pain, regional block anesthesia, thoracoscopic surgery